Judge’s View Of Negligence Criminal Acts Which Cause Death In Traffic Scope - Heri Joko Purnomo; Gunarto Gunarto (Law Development Journal, 2020)
The purpose of this research isto study, know and analyze the judge's point of view in the verdict of a case of negligence that causes the death of another person within the scope of traffic. In this study, the authors used sociological juridical methods with descriptive research specifications. The data used for this research are primary and secondary data. Based on the research, it was concluded that in positive law, the Defendant RK in case Number 186 / Pid.Sus / 2018 / PN.Jpa positively violated the provisions in accordance with the aggravating matter, namely the Accused's negligence caused the death of another person and also the Defendant did not have standardization driving license in the form of a driving license (SIM).